Chemical examination of Hydrocotyle bonariensis L. (Apiaceae) - Lien Huong, Ton Nu; Phi Phung, Nguyen Kim; Suong, Nguyen Ngoc (Vietnam Journal of Chemistry, 2014)
Hydrocotyle bonariensis, growing in the Mekong-delta, is used as vegetable and has not yet been chemically studied. From the aerial parts of H. bonariensis, three compounds had been isolated: a triterpene squalene (1) and a mixture of two lignans: hinokinin (2) and α-[3,4-methylendioxy phenylmethylidene]-β-[3,4-methylendioxyphenylmethyl]-γ-butyrolactone (3). The fresh plant was divided into stem-leaf and flower and each part was distilled with steam to afford essential oils. The major components of stem-leaf are: (Z)-3-hexen-1-ol, trans-caryophyllene, α-farnesene, copaene while the major components of flower are: α-pinene, 2-β-pinene, β-myrcene, limonene, α-caryophyllene, epibicyclosesquiphellandrene. The essential oil of the stem-leaf showed cytotoxic activities in vitro on RD and Hep-G2 cancer cells with the IC50 values of 16.1 and 19.9µg/ml, respectively. The study on the plant is being continued.